Flatwise Testing Modeling Study On Aluminium Honeycomb Panel - Ramayanti, Sri (Indonesian Journal of Aerospace, 2022)
Honeycomb sandwich structures are widely used in space applications due to their exceptional performance. Extensive research has been conducted on the response of honeycomb structures to various external loads. The out-of-plane strength, including compression and tensile properties, is a critical aspect of honeycomb structures. Despite some experimental and numerical studies, research specifically addressing the tensile direction, such as flatwise tensile testing in honeycombs, remains limited. This testing focuses on the bond strength between the face sheets and the honeycomb core, as well as the tensile strength of the core itself. Utilizing finite element analysis (FEA) has proven effective for characterizing honeycomb structures under various load conditions. However, the complex geometry of the core requires an enormous number of elements, increasing computation times. Thus, simplifying the model by replacing the hexagonal geometry with a homogenized solid layer with effective material properties is necessary. This study focuses on flatwise tensile testing of aluminum honeycomb using different modeling approaches: discrete, continuum, and equivalent plate models. The discrete model serves as the reference due to its detailed structural representation. The continuum-Gibson model, while reasonably accurate in stress estimation, tends to overestimate displacement. Both equivalent models, Hoff and Reissner, significantly overestimate displacement, with Hoff underestimating stress and Reissner overestimating it. In contrast, equivalent models offer insights, but their accuracy varies, necessitating further calibration for precise predictions. Future research should validate these simulation results with real tests.